Evaluation of Botanical and Synthetic Insecticide for the Control of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) - Iram, Naima; Arshad, Muhammad; Akhter, Naheed (BioAssay, 2013)
Research studies were carried out to evaluate insecticidal action of two plant products and a synthetic insecticide on a major stored-product insect, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae). The plant species studied were, Psidium guajava (L.) (Guava, leaves; Myrtaceae) and Citrus reticulata (Kinnow, peel and leaves; Rutaceae). Methoprene was used as synthetic insecticide. Two formulations viz., powder and ethanol extract of each plant and four concentrations (5, 10, 15 and 20%) of methoprene were tested. Repellency was tested using the filter paper test whereas mortality, weight loss protection and anti-feedant potential of all treatments was evaluated by using whole wheatgrains. Our results reported that all tested treatments had significant effects pertaining to all variables analyzed and ethanol extract was found to be remarkably more potent than powder form of same plant. Furthermore, leaves and peel of C. reticulata did not differ significantly pertaining to their toxicity against adult T. castaneum but stronger than P. guajava whereas, activity of methoprene was comparableto of botanicals at concentration of 20 ppm.